Gene Transfer of Interleukin 10 to the Murine Cornea Using Electroporation - Zhou, Rui (Exp Biol Med (Maywood), 2007)
Gene therapy is a promising approach to deliver anti-inflammatory genes to the eye to treat a number of corneal diseases. We have used electroporation to deliver plasmids expressing interleukin 10 (IL-10) to the corneas of mice and evaluated the duration of expression following gene transfer. Unlike expression of reporter genes driven from the cytomegalovirus immediate early promoter (CMV(iep)), which remained high for 3 days, CMV(iep)-driven IL-10 expression peaked at Day 1 and decreased 2-fold each day thereafter. In an attempt to increase the duration of expression, the long-acting ubiquitin C (UbC) promoter was used but, surprisingly, a similar half-life of gene expression was observed. This reduced duration was not due to promoter inhibition by expressed IL-10 or clearance of plasmids from the cornea. However, when DNA nuclear targeting sequences (DTSs) that promote DNA nuclear import were removed from the plasmids, contrary to findings in nondividing cells and tissues in which these sequences are needed for gene transfer, robust expression was observed, and the duration increased significantly. Although corneal cell turnover was detected, suggesting mitosis-dependent plasmid nuclear localization independent of a DTS, the patterns of expressing and dividing cells appeared different. These results suggest that DNA nuclear targeting sequences may act differently in the cornea than in other tissues.